An analytical study of the dimerization of in vitro generated RNA of Moloney murine leukemia virus MoMuLV. - Roy, C (1990)
The genome of Moloney murine leukemia virus(MoMuLV) is composed of two identical RNA molecules joined at their 5' ends by the dimer linkage structure (DLS). Recently it was shown that in vitro generated MuLV RNA formed dimeric molecules and that dimerization sequences are located within the Psi encapsidation domain between positions 215 and 420. Conditions for the spontaneous dimerization of a MuLV RNA fragment encompassing the Psi domain have been investigated. The rate of spontaneous MuLV RNA dimer formation is dependent upon RNA, NaCl and MgCl2 concentrations as well as temperature. Thermal denaturation of in vitro generated dimer RNA of 350 nt, from positions 215 to 565, gave a Tm of about 58 degrees C in 100 mM NaCl. This Tm value is very close to that found for RNA corresponding to the 5' 755 nt and to the genomic 70 S RNA isolated from virions. According to thrermodynamic parameters derived from denaturation curves of MuLV dimer RNA generated in vitro, the dimer linkage structure probably involves short sequences.